PMO implementation in trinidad and tobago engineering-service contractor firms: challenges and lessons learned - Mahabir, Randell Jared; Mahabir, Roneil Jareth (International Journal of Industrial Optimization, 2022)
This paper explores the challenges and lessons learned in integrating a project management office (PMO) into the existing organizational structure of engineering-service contractor (ESC) companies in Trinidad and Tobago (T&T). Although several T&T ESCs now boast of having a robust PMO, its implementation has been a difficult and expensive endeavor for most, persuading others to forego this. This disinclination is due to the lack of available insight and guidance on PMO implementation for ESCs operating in the Caribbean. Top management personnel and departmental managers from twenty-eight ESCs who played a direct role in the PMO incorporation at their organizations were polled in a self-report study which collected quantitative data via a questionnaire. Insights on their perceived PMO value, implementation weak and strong points, integration challenges and lessons learned were gathered and analyzed. The findings confirmed concurrence amongst all participating ESCs that PMO implementation bodes well for their strategic organizational goals. The biggest implementation challenges reported were creating a project management culture and realigning the power for resource management and allocation. Smoother integration was reported amongst companies that included suitable communication channels, pre-implementation planning, and project management training for PMO personnel into the process. For the findings varied across companies, this paper illustrates numerous areas of concern common to ESCs. There is no existing research on PMO implementation in T&T or Caribbean firms, and this paper provides foresight and direction for companies contemplating such endeavors.